2017
DOI: 10.1124/jpet.116.239608
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phosphodiesterase 4 Inhibitor FCPR03 Alleviates Lipopolysaccharide-Induced Neuroinflammation by Regulation of the cAMP/PKA/CREB Signaling Pathway and NF-κB Inhibition

Abstract: Overactivation of microglia contributes to the induction of neuroinflammation, which is highly involved in the pathology of many neurodegenerative diseases. Phosphodiesterase 4 (PDE4) represents a promising therapeutic target for anti-inflammation; however, the dose-limiting side effects, such as nausea and emesis, have impeded their clinic application. FCPR03, a novel selective PDE4 inhibitor synthesized in our laboratory, shows little or no emetic potency; however, the anti-inflammatory activities of FCPR03 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…In particular, PDEs play a crucial role in controlling the magnitude and the duration of PKA signaling [ 37 ]. Given this key function of PDEs and the established link between PDE4 and inflammatory responses in microglia [ 38 41 ], we investigated whether LRRK2 activity affects cAMP levels in microglia. We found that cells treated with LRRK2 kinase inhibitor exhibit increased levels of cAMP compared to control cells, indicating that LRRK2 activity affects cAMP degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PDEs play a crucial role in controlling the magnitude and the duration of PKA signaling [ 37 ]. Given this key function of PDEs and the established link between PDE4 and inflammatory responses in microglia [ 38 41 ], we investigated whether LRRK2 activity affects cAMP levels in microglia. We found that cells treated with LRRK2 kinase inhibitor exhibit increased levels of cAMP compared to control cells, indicating that LRRK2 activity affects cAMP degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PDE4 is effective to suppress the production of IL-1. Our previous studies have shown that inhibition or silencing of PDE4 attenuated the level of IL-1β in β amyloid-injected mice 50 , APP/PS1 transgenic mice 119 and lipopolysaccharide-treated mice 14 , 130 . Consistently, another independent study showed that the SNPs in the PDE4D (83T/C) and IL-1 (-889C/T) were related with high risk of the occurrence of ischemic stroke 131 .…”
Section: Inhibition Of Pde4 Restricts Neuroinflammation In the Brain mentioning
confidence: 99%
“…Among various PDE family proteins, phosphodiesterase 4 (PDE4) specifically hydrolyzes cAMP and inhibition of PDE4 is an ideal strategy for the prevention and treatment of peripheral inflammation and immune diseases, such as pulmonary inflammation and psoriasis 13 . In the CNS, PDE4 plays a key role in both chronic neurodegenerative diseases and acute neurological insults, including stroke 14 , 15 . Recently, an increasing number of reports have shown that inhibition of PDE4 is beneficial for neuroplasticity 16 - 18 , making it a promising candidate target that has therapeutic potential for the recovery of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , FCPR03 inhibited the immune responses in LPS-stimulated BV-2 cells, a microglial cell line, and its anti-inflammatory effects could be blocked by a PKA inhibitor, H89. In vivo , FCPR03 suppressed pro-inflammatory mediators by increasing the level of cAMP, promoting CREB phosphorylation, and inhibiting NF-κB activation in the cortex and hippocampus of LPS-immunized mice (Zou et al, 2017 ). Furthermore, a study in mice challenged by LPS found that 1 mg/kg/day FCPR03 showed anti-depressant effects as confirmed by the decrease in depressant-like behaviors with the duration of immobility in the forced swim and tail suspension tests (Yu et al, 2018 ).…”
Section: Pde4 Inhibitors Under Development For the Treatment Of Inflamentioning
confidence: 99%